The Effect of the Intervention of William Glasser's Reality Module ('D'RWG) on Drug Abuse Among Young Residents of the Cure and Care Rehabilitation Clinic (CCRC) - Thivya Khalidass; Saralah Devi Mariamdaran Chethiyar; Venothiney Dewi Muniandy (International Journal of Qualitative Research, 2021)
This study was conducted to see the effect of the Intervention of William Glasser's Doing Reality Module ('D'RWG) on drug abuse among young residents of the Cure and Care Rehabilitation Clinic (CCRC). The objective of this study is to analyze the factor of drug abuse, to examine the steps to be taken to overcome the factor of drug abuse, and to know the effect of the 'Doing Reality William Glasser' ('D'RWG) module on drug abuse among the residents of the Care and Cure Rehabilitation Clinic (CCRC). The study was conducted at a Cure and Care Rehabilitation Clinic located in Kedah. This study involved eight respondents. This study is in the form of qualitative which was conducted through face-to-face interviews. The data were analyzed using three themes: (1) affection towards the family (2) family ecology, community and cultural factors, and (3) prevention and education programs. The findings showed that all respondents were able to give their ideas and share experiences while engaging in drug abuse. Respondents were also able to provide some suggestions to combat drug abuse symptoms, especially in adolescents.